Immediate outcome of neonates with maternal hypertensive disorder of pregnancy at a neonatal intensive care unit (Northern International Medical College Journal, 2015)
Aims : Hypertensive disorders in pregnancy remain a major cause of maternal and neonatal morbidity and mortality worldwide. This study prospectively examined the immediate neonatal outcome of women with maternal hypertensive disorder of pregnancy( HDP).Methods : Sixty mothers and their newborn were selected. Mothers with gestational hypertension, preeclampsia, preeclampsia superimposed on chronic hypertension and chronic hypertension were included.Results : Forty five (75%) mothers were mutipara and 15(25%) were primipara. Mean maternal age was 26.4 years. Mean gestational age was 34+4 weeks. 38 were male and 22 were female with Male: Female ratio was 1.72: 1. Thirty six (60%) were from in patient with regular antenatal check up, 60% mothers had gestational hypertension. Fifty four (90%) mothers needed lower uterine caesarian section. Forty four (73.33%) delivered preterm before 36 weeks of pregnancy. Low birth weight (